Historical significance of Gojong's transition in Russian diplomatic mission - Lapina N. G. (Scientific community of students, 2016)
the author points out that in the late XIX century in a sharpening of capitalist powers struggle for influence in Korea and unstable political situation van Gojong along with the heir to the throne had taken refuge in the territory of Russian diplomatic mission in Seoul, where he managed to fulfill the state administration. The article provides an analysis of the events that preceded the transition of Korean ruler to Russian diplomatic mission, as well as an attempts to assess the incident and to identify its impact on Russian-Korean relations.
Keywords: Россия; Russia; дипломатия; Корея; дипломатические отношения; российско-корейские отношения; Коджон; Korea; diplomatic relations; diplomacy; Russian-Korean relations; Gojong; японо-китайская война; Sino-Japanese War